2019
DOI: 10.1371/journal.pgen.1007721
|View full text |Cite
|
Sign up to set email alerts
|

Locus suicide recombination actively occurs on the functionally rearranged IgH allele in B-cells from inflamed human lymphoid tissues

Abstract: B-cell activation yields abundant cell death in parallel to clonal amplification and remodeling of immunoglobulin (Ig) genes by activation-induced deaminase (AID). AID promotes affinity maturation of Ig variable regions and class switch recombination (CSR) in mature B lymphocytes. In the IgH locus, these processes are under control of the 3’ regulatory region (3’RR) super-enhancer, a region demonstrated in the mouse to be both transcribed and itself targeted by AID-mediated recombination. Alternatively to CSR,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…The same study showed that disease-associated SNPs occur in superenhancers of disease-relevant cells and that this occurs more frequently in superenhancers than in typical enhancers. Recent evidence has also been provided for a role of 3 0 RRs in the so-called locus suicide recombination occurring during B cells maturation (Dalloul et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same study showed that disease-associated SNPs occur in superenhancers of disease-relevant cells and that this occurs more frequently in superenhancers than in typical enhancers. Recent evidence has also been provided for a role of 3 0 RRs in the so-called locus suicide recombination occurring during B cells maturation (Dalloul et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The model used in our laboratory facilitates the study of B cell development from NBCs to the plasmablast stage and allows to visualize at molecular level any modifications occurring either early or late during the maturation process ( 6 8 , 109 111 ). Indeed, this paper brings new elements concerning the regulation of PERK and some factors that could have an impact on the productivity of mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…NGS also allowed us to simplify TCR and BCR repertoire evaluation through the Rep-Seq technique [ 94 ]. For instance, BCR profiling led to a better understanding of an alternative to an isotypic switch in the B cell (locus suicide recombination), resulting in the deletion of a constant region that could restrain the activation of mature B cells [ 95 ]. Technologies depicting the Ig repertoire and evaluating the redundancy of clonal sequences have been found to be valuable in multiorgan diseases [ 96 ] but also in vaccination [ 97 ].…”
Section: High-throughput Immunomonitoring Techniquesmentioning
confidence: 99%